PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS SEARCH SOLVE CREATE (SSCS) PAD MATERI BANGUN DATAR SEGI EMPAT DI KELAS VII SMP NEGERI KARANG DAPO - Rati Auwallah; Efuansyah E; Rani Refianti (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to develop a Search Solve Create Share (SSCS) based student worksheet on class VII quadrangular flat building materials. This research is development research using a 4-D development model consisting of 4 stages, namely: the defining stage (define), the planning stage (design), the development stage (develop), and the deployment stage (disseminate). The results showed that the SSCS-based LKS developed met valid and practical criteria. SSCS-based LKS is included in the